2005
DOI: 10.1364/ao.44.004523
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of wave-front aberration in soft contact lenses by use of a Shack–Hartmann wave-front sensor

Abstract: Lower- and higher-order wave-front aberrations of soft contact lenses were accurately measured with a Shack-Hartmann wave-front sensor. The soft contact lenses were placed in a wet cell filled with lens solution to prevent surface deformation and desiccation during measurements. Aberration measurements of conventional toric and multifocal soft contact lenses and a customized soft contact lens have proved that this method is reliable. A Shack-Hartmann wave-front sensor can be used to assess optical quality of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 11 publications
1
29
0
Order By: Relevance
“…However, little is known about the mechanism of reducing contrast sensitivity following the wearing of tinted contact lenses. In clear (nontinted design) soft contact lenses, the impact on higher-order wavefront aberrations [6][7][8][9] and the relationship between higher-order aberrations and visual performance [10][11][12][13] have been extensively investigated. Changes in higherorder aberrations after wearing tinted contact lenses, however, have never been studied.…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the mechanism of reducing contrast sensitivity following the wearing of tinted contact lenses. In clear (nontinted design) soft contact lenses, the impact on higher-order wavefront aberrations [6][7][8][9] and the relationship between higher-order aberrations and visual performance [10][11][12][13] have been extensively investigated. Changes in higherorder aberrations after wearing tinted contact lenses, however, have never been studied.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20] Wavefront measurements also have been recorded to evaluate the optical performance of contact lenses. [21][22][23][24][25] Studies measuring wavefront aberrations in eyes with and without contact lenses reported that soft or rigid gas-permeable contact lens wear causes changes in the ocular wavefront aberrations. [22][23][24] Recently, Jeong et al 25 assessed the aberrations of toric soft contact lenses, multifocal soft contact lenses, and customized soft contact lenses with a wavefront sensor.…”
mentioning
confidence: 99%
“…[21][22][23][24][25] Studies measuring wavefront aberrations in eyes with and without contact lenses reported that soft or rigid gas-permeable contact lens wear causes changes in the ocular wavefront aberrations. [22][23][24] Recently, Jeong et al 25 assessed the aberrations of toric soft contact lenses, multifocal soft contact lenses, and customized soft contact lenses with a wavefront sensor. However, because fluctuating or blurry vision is common in symptomatic wearers of soft contact lenses, one measurement of wavefront aberrations may not detect sequential alterations in optical quality during contact lens wear.…”
mentioning
confidence: 99%
“…For our cylindrical lens, these parameters were measured with a Shack-Hartmann wavefront sensor (Thorlabs, WFS series) [21][22][23][24]. Based on the results, our device showed modest aberrations since the measured aberrations (i.e., coma, tilt, spherical aberration, astigmatism) were modest and comparable to those measured from the same commercial refractive lens described above, as shown in Table 1.…”
Section: Resultsmentioning
confidence: 63%